Radiation Oncology reviewer acknowledgment 2012 - Belka, Claus (BioMed Central, 2013)
CONTRIBUTING REVIEWERS: The editor of Radiation Oncology would like to thank all our reviewers who have contributed to the journal in Volume 7 (2012).